A high-throughput, solvent free method for dispersing metal atoms directly onto supports. Issue 47 (24th November 2021) - Kohlrausch, Emerson C.; Centurion, Higor Andrade; Lodge, Rhys W.; Luo, Xuanli; Slater, Thomas; Santos, Marcos J. L.; Ling, Sanliang; Mastelaro, Valmor R.; Cliffe, Matthew J.; Goncalves, Renato Vitalino; Alves Fernandes, Jesum
Abstract : Atomically-dispersed metal catalysts (ADMCs) on surfaces have demonstrated high activity and selectivity in many catalytic reactions. Abstract : Atomically-dispersed metal catalysts (ADMCs) on surfaces have demonstrated high activity and selectivity in many catalytic reactions. However, dispersing and stabilising individual atoms in support materials in an atom/energy-efficient scalable way still presents a significant challenge. Currently, the synthesis of ADMCs involves many steps and further filtration procedures, creating a substantial hurdle to their production at industrial scale. In this work, we develop a new pathway for producing ADMCs in which Pt atoms are stabilised in the nitrogen-interstices of a graphitic carbon nitride (g-C3 N4 ) framework using scalable, solvent-free, one-pot magnetron sputtering deposition. Our approach has the highest reported rate of ADMC production of 4.8 mg h −1 and generates no chemical waste. Deposition of only 0.5 weight percent of Pt onto g-C3 N4 led to improved hydrogen production by factor of ca. 3333 ± 450 when compared to bare g-C3 N4 . PL analysis showed that the deposition of Pt atoms onto g-C3 N4 suppressed the charge carrier recombination from the photogenerated electron–hole pairs of Pt/g-C3 N4 thereby enhance hydrogen evolution. Scanning transmission electron microscope imaging before and after the hydrogen evolution reaction revealed that the Pt atoms stabilised in g-C3 N4 have a high stability, with no agglomeration observed. Herein, it is shown that this scalable and clean approach can produce effective ADMCs with no further synthetic steps required, and that they can be readily used for catalytic reactions.